Pengenalan dan Pelatihan Mesin Produksi untuk Pengrajin Batik di Bojonegoro - Putra, S.E., MSA, Rediyanto; Nerisafitra, Paramitha; Abidin, Asroful (Universitas Negeri Surabaya, 2024)
The batik artisan business in Indonesia is one of the businesses that has experienced significant development. Bojonegoro Regency is one of the districts in East Java Province that has a characteristic motif in the batik industry. A typical batik motif from Bojonegoro Regency is the pari sumilak motif which has the meaning of a rice motif that will be ready for harvest. Therefore, in this community service activity, we will carry out activities at one of the batik businesses in Bojonegoro Regency, namely Sesa batik. Sesa batik business is located in Dusun.kajangan RT.16/RW.04 Jono Village, Temayang District, Bojonegoro Regency, East Java Province. This community service activity aims to provide solutions related to the problem of batik cloth production in the Sesa Batik business, namely related to the batik cloth drying process, where the batik cloth drying process is still carried out traditionally, namely by using sunlight. Therefore, in this service, the introduction and training of batik cloth drying machine technology and batik wax heaters will be carried out so that partner productivity is better. The results of this service activity are 2 production machine technologies that are introduced and trained to partners, namely batik cloth drying machine technology and batik wax heaters. The partners stated that the existence of these two technologies really helped the batik cloth production process because these two machines have temperature regulators that can determine how hot the temperature needed to dry the batik cloth and heat the batik wax.